Labdane and pimarane diterpenes from Croton joufra - Somyote Sutthivaiyakit (2018)
From the chloroform extract of the leaves of Croton joufra, the diterpenes 2α,3α-dihydroxy-labda-8(17),12(13),14(15)-triene and 3β-hydroxy-19-O-acetyl-pimara-8(9),15-dien-7-one, were isolated. Their structures were establised by spectroscopic methods. One of the compounds showed weak lethality in the brine shrimp assay. © 2001 Elsevier Science Ltd.